Superstars and mediocrities: a solution based on personal income taxation - Diego d'Andria (European Commission, Joint Research Centre (JRC), 2018)
The markets for talent often produce large income inequality and therefore raise political attention. While such inequality can be due to superstar dynamics or factor complementarities, Terviö ("Superstars and Mediocrities: Market Failure in The Discovery of Talent", the Review of Economic Studies, 2009) first proposed a market failure that was previously unknown to the literature, pointing to long-term contracts as a solution. I extend the model in Terviö (2009) to include personal income tax policy reforms and demonstrate that tax design can be employed as a solution to the market failure when long-term contracts are unfeasible. With small enough entry payments that novice workers would sustain to compensate employers for the cost of learning, both a progressive tax and a tax incentive on entry wages are found effective. The tax incentive on entry wages, though, can be used even with very large deductible entry payments and with overall negative net entry wages.
Keywords: H21; H24; J31; J6; 330; superstars; personal income tax; entry wage; talent; learning